2015
DOI: 10.3389/fgene.2015.00037
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes as targets in hereditary hemorrhagic telangiectasia

Abstract: Defective paracrine Transforming Growth Factor-β (TGF-β) signaling between endothelial cells and the neighboring mural cells have been thought to lead to the development of vascular lesions that are characteristic of Hereditary Hemorrhagic Telangiectasia (HHT). This review highlights recent progress in our understanding of TGF-β signaling in mural cell recruitment and vessel stabilization and how perturbed TGF-β signaling might contribute to defective endothelial-mural cell interaction affecting vessel functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 162 publications
1
38
0
1
Order By: Relevance
“…40 Histologically, angiodys-plasia is associated with endothelial proliferation and pericyte loss. 3,4 Studies have suggested TNF-α/Ang-2 synergy leads to pericyte apoptosis. 13,41 Herein we found TNF-α–induced pericyte apoptosis in LVAD patients is associated with suppression of Ang-1, which is blunted by TNF-α blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Histologically, angiodys-plasia is associated with endothelial proliferation and pericyte loss. 3,4 Studies have suggested TNF-α/Ang-2 synergy leads to pericyte apoptosis. 13,41 Herein we found TNF-α–induced pericyte apoptosis in LVAD patients is associated with suppression of Ang-1, which is blunted by TNF-α blockade.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, the under-lying mechanism remains unknown. Angiodysplasia is associated with endothelial proliferation and decreased vessel coverage by pericytes, 3,4 non-endothelial vascular cells that support the endothelium. Pericytes produce angiopoietin-1 (Ang-1), an agonist of Tie-2, 5 which promotes vessel stability.…”
mentioning
confidence: 99%
“…The endoglin, ALK1, and SMAD4 proteins are components of the transforming growth factor-β/bone morphogenetic protein signaling pathways: ALK1 is a type I transmembrane serine threonine receptor kinase, endoglin is an auxiliary receptor, and SMAD4 is the common partner for canonical (SMAD-based) signaling [5] . While the exact pathogenic mechanisms are yet to be determined, vascular abnormalities in HHT are thought to arise due to resultant imbalances in the response to angiogenic factors such as vascular endothelial growth factor [6] , defective vascular repair [7] , and/or modified vessel maturation [8] . Recently, heterozygous missense substitutions in the GDF2 gene, which encodes bone morphogenetic protein 9, have been reported in individuals with some cutaneous vascular lesions similar to those seen in HHT [9,10] , although the pathogenicity of the gene variants remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this data adds to the growing body of evidence for a pleiotropic role of BMP9 in development and disease. While a defective paracrine signaling between endothelial cells and the neighboring mural cells may be one of the underlying causes of HHT (Thalgott et al., 2015), neutralization of BMP9 in tumor angiogenesis may lead to opposing effects, as indicated by increased numbers of pericyte covered tumor vessels.…”
Section: Discussionmentioning
confidence: 99%